The ameliorative effects of selenium nanoparticles (SeNPs) on diabetic rat model: a narrative review - Anas Ahzaruddin Ahamad Tarmizi,; Siti Hajar Adam,; Nik Nasihah Nik Ramli,; Nur Ahfizah Abd Hadi,; Abdul Mutalib Maisarah,; Gee, Shirley Hoon Tang; Mohd Helmy Mokhtar, (Penerbit Universiti Kebangsaan Malaysia, 2023)
The emergence of nanotechnology has become more popular, and the progress had sparked much development in nanoparticle synthesis, including selenium. Studies associated with the therapeutic abilities and physicochemical properties of selenium nanoparticles (SeNPs) are rapidly growing and gaining interest from many researchers. This review discusses on the fundamental components of selenium, different approaches in synthesizing selenium nanoparticles, its remedial properties and potential in biomedical application. Herein, primary focus will be given to the action of selenium nanoparticles mechanism in improving diabetes mellitus symptoms and complications in animal studies. It is known that selenium is an important micronutrient found in humans, plants and animals that can be incorporated as selenoprotein in the human body. Analysis and comparison on the findings enlighten that SeNPs demonstrated ameliorative effect on diabetes complications due to their antidiabetic, antioxidant, anti-inflammatory and lipid-lowering characteristics.